PENGARUH KERAGAMAN PRODUK, HARGA DAN LOKASI TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA TOKO BARU SENANG - Indriani, Shafa Arina; Hamdun, Edy Kusnadi; Syahputra, Hendra (Fakultas Ekonomi dan Bisnis, 2024)
The aim of the research is to determine the influence of product diversity, price and location on purchasing decisions through consumer decisions as an intervening variable at the Baru Senang Store. The sampling technique in this research is simple random sampling. Data analysis and hypothesis testing in this research used Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that product diversity has a significant positive effect on purchasing decisions, price has a significant positive effect on purchasing decisions, location has a significant positive effect on purchasing decisions, product diversity has a significant positive effect on consumer satisfaction, price has a significant effect positive effect on consumer satisfaction, location has a positive but not significant effect on consumer satisfaction, purchasing decisions have a significant positive effect on consumer satisfaction, product diversity has a significant positive effect on consumer satisfaction through purchasing decisions, price has a significant positive effect on consumer satisfaction through purchasing decisions, location has a positive effect on satisfaction consumers through purchasing decisions have a significant positive effect,